Understanding Generation Z's Ecotourism Motivation and Perception in Central Sulawesi - Rif'an, Afief; Maarif, Fadjri; Situmorang, Delima Ayu Gustina (Jurnal Wasian, 2024)
The emergence of Generation Z, which constitutes the majority of Indonesia's population, has the potential to drive national progress and promote environmental sustainability. This study aims to explore Generation Z's motivations toward ecotourism and examine their perceptions of ecotourism in Central Sulawesi. A qualitative research approach was employed, utilizing interviews and questionnaires as data collection methods. Respondents consisted of individuals from Generation Z (aged 11–27 years) residing in Central Sulawesi. Likert scale analysis was used to measure the level of motivation and perception among Generation Z regarding ecotourism. The findings reveal that Generation Z's motivation for ecotourism is influenced by both internal and external factors, with internal motivation being slightly more dominant (a difference of 0.23%). Furthermore, the study indicates that Generation Z's perception of ecotourism in Central Sulawesi reflects limited awareness and understanding of conservation values and environmental sustainability. Improvements in facilities and service quality were found to positively influence Generation Z's perception of ecotourism. The study concludes that enhanced development efforts can strengthen both motivation and perception, thereby increasing participation levels and fostering a positive impact on ecotourism.